Self-efficacy dan kemampuan pemecahan masalah siswa SMP pada materi barisan dan deret aritmatika - Saetban, Iche Imelda; Jamiah, Yulis; Yusmin, Edy; Yani, Ahmad; Siregar, Nurfadilah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Finding out how well one can solve issues involving mathematical sequences and series is the primary goal of this study. The confidence that students feel after they have solved a problem is strongly correlated with their problem-solving ability, which is why this study was carried out. A quantitative technique based on survey methodology is used in this study. Thirty students from class IXA at SMPN 8 Pontianak made up the sample for this research, which used basic random sampling to determine the population. The tool used consisted of a 26-statement self-efficacy questionnaire with Likert scale measurements and a 4-question problem-solving skill test with four indications. The results were examined by using the Spearman Rank method to the collected data. Since the study data included both ordinal and interval variables, the Spearman Rank method was used. Findings indicated that self-efficacy and problem-solving skills were unrelated.